The Role of Medical Physics in the Design and Optimization of Diagnostic Imaging Devices - Awied, Mohamed Raed; Abdelnabi , Ali Mohammed; Mohammed, Fatima Salem Jassim (American Journal of Botany and Bioengineering, 2025)
To explore the role of medical physics in the design and optimization of diagnostic imaging devices, it is essential to focus on physical aspects of these devices. The focus here is on physical optimization of digital x-ray detection systems primarily because of the extensive background and experience in this area and also because of current interest in clinical applications of x-ray tomosynthesis with systems still being manufactured and marketed based on experience accumulated in a different area – digital x-ray radiographic systems. Others have examined other aspect of such devices and their use. Varied aspects of digital radiographers have been thoroughly examined so breadth of coverage would be a huge task. Already substantial content has been collected and organized into 30-papers on complementary topics covering the many areas of interest and need. Digital x-ray imaging has several important advantages over conventional analog systems. Instead of film and screen detectors, cost-effective, image intensifier and video cameras, lattice photo-diodes and video, and separate image processors, these imaging devices are being replaced simply with a digital detector, a computer workstation and a printer. Illumination and handling of the films, film-screens, and their storage and retrieval are no longer worries. The film also becomes a permanent image without any risk of patient privacy breach from wrong storage and retrieval. The latest advantage, increased diagnostic confidence, is in part a consequence of the variably enhanced imaging performance and optimized parameter settings made possible by digital systems. Interesting and promising applications are also appearing. The digital x-ray exposures depend on the x-ray beam describing a specific view through the imaged volume of tissue. Unlike film, the electronic detectors are capable of capturing in real-time the intensity of the incoming x-rays composing this view with either some or no geometrical compression in storage depending on individual devices. Instead of silver grains, x-ray quanta interacting with these grids excite free charges in the solid or transferred through scintillation. The quanta intensities are captured as either real "analog" pixel corresponding to their locations or as grayscale values of discretely defined finite elements in the grid while weights are more instructively shown rank-wise.